An Online Method to Study Remote Operation of Automated Vehicles. (September 2022) - Morrison, Danielle; Cui, Lingfan; Feng, Jing
Remote operation is an emerging technical component of vehicle automation. One scenario could be a remote operator monitors the functioning of automation and take over vehicle control whenever needed. As the operator may face challenges such as degraded situation awareness or vigilance decrement, it is important to understand operator performance in a variety of takeover scenarios. This study presents an effort to create an online method for studying remote takeover performance. In this study, participants were presented with simulated driving videos and were required to indicate when they felt a takeover was needed. To ensure quality data collection in an online procedure, we made specific considerations when implementing the study. In this paper, we address these considerations and present preliminary data. Our findings suggest that operators may be less able to detect certain automation failures such as disobedience of road signs, and the online method could be useful although with limitations.